PENGEMBANGAN MULTIPLE INTELLIGENCES MELALUI PEMBELAJARAN KREATIF DI RUMAH KREATIF WADAS KELIR (RKWK) KELURAHAN KARANGKLESEM RT 07/05 KECAMATAN PURWOKERTO SELATAN KABUPATEN BANYUMAS - Rofik andi hidayah (IAIN Purwokerto, 2015)
Abstract: The results of this paper indicate that the implementation of the development of multiple intelligences in the Wadas Kelir Creative House (RKWK) is done through creative learning, ie leaming-based games to develop children's creativity in accordance with the potential of intelligence has, especially 5 (five) intelligence developed, namely language intelligence (linguistic-verbal), numbers intelligence (logical-mathematical), picture intelligence (visual-spatial), body intelligence (kinesthetic), and musical intelligence. However, other intelligence such as social-interpersonal intelligence, self-reflection intelligence (intrapersonal) and naturalistic intelligence also can not be neglected in leaming activities and become an integral part in it. The workleaming products children were sent to the media and exhibited and performed in a particular activity or event. Keywords: Multiple Intelligences, Creative Leaming, Rumah Kreatif Wadas Kelir (RKWK).